THE ACCEPTABILITY OF TELEMEDICINE IN POST-MASS CHARITY CIRCUMCISION IN INDONESIA: A PILOT STUDY - Aulia, Indri; Valeria, Michelle; Zacharia, Nathaniel J.; Amangku, Bagus R.; Prasetyo, M. Luthfi (Jurnal Plastik Rekonstruksi, 2023)
Introduction: Charity circumcision is common in Indonesia. It is usually done by general practitioners or medical students under supervision. Procedures are often held on a mass scale and rarely followed with post-monitoring. We developed a telemedicine follow-up protocol to educate and address post-procedure complications. This pilot study evaluates the acceptability of telemedicine follow-up protocol for charity circumcision in Indonesia. Method: Data were collected from operators and caregivers of children attending charity circumcision. The protocol consisted of text interviews (pain, urinary retention) and surgical sites' four-angle photographs (epithelialization, bleeding, infection, edema, and glans excoriation). The protocol was conducted two-way between caregivers and operators on days 1, 3, 7, and 30 after circumcision. The Ethics Committee of the Faculty of Medicine, Universitas Indonesia, has approved this study. Result: Twenty-five boys with a mean age of 8.02±1.53 years old have similar pre-operative, operative, and postoperative protocols. Twenty-one caregivers completed four times follow-ups, one missed two times follow-ups, and three missed the last follow-up. Mild pain was the most reported complication, with 32% (8/25), 12% (3/25), 8% (2/24) incidence on days 1, 3, and 7, respectively. By the end of the follow-up, there were no persisting complications, and 80% (20/25) of boys showed complete epithelialization. All caregivers and most operators were satisfied with telemedicine for post-mass circumcision monitoring. Conclusion: The telemedicine-based follow-up is acceptable and feasible to be applied in mass charity circumcision. This protocol is beneficial for monitoring the results and adverse events, therefore, should be routinely adopted in mass charity circumcision programs.